Land, Language, and Leadership: Two-Eyed Seeing in British Columbia’s Natural Resource Management - Atleo, Tara (Journal of Aboriginal Economic Development)

(untitled) (CANDO, 2025)
Indigenous law and governance systems across British Columbia have experienced tremendous hardship and transformation since first contact. Colonial systems have stifled Indigenous cultural governance structures, compromising Indigenous communities’ centuries-old methods of sustainable land and resource management through stewardship. Despite the acknowledged importance of Indigenous stewardship in natural resource management initiatives, land-based decision making within British Columbia continues to design and implement processes and mechanisms that stifle Indigenous law and governance and misrepresent Indigenous values.This article uses document analysis of 123 forestry-centric government-to-government Forest Consultation and Revenue Sharing Agreements within British Columbia to explore how Two-Eyed Seeing manifests through the opportunity to uphold Indigenous law and governance in these agreements. Focusing on the use of Indigenous language, cultural values, and hereditary leadership, nine of the agreements studied showed signs of Indigenous law and governance in their terms. These findings highlight the need for a path forward that is inclusive and empowers Indigenous law and governance in natural resource decision making to ensure enhanced stewardship opportunities for future generations.